Trade in Financial Services: Procompetitive Effects and Growth Performance - Joseph F. Francois; Lutger Schuknecht (Tinbergen Institute, 1999)
In this paper we explore linkages between financial services tradeand growth. We offer aformalization of the argument that trade, through the fostering offinancial market integration,may yield important long-run effects related to increasedcompetition. The relationshipsformalized here link long-run economic performance to scale economiesand cost structures inthe financial services sector, and to market concentration in thesector. We first develop ananalytical model. This motivates an econometric exercise. Cross-country growth regressionspoint to a strong positive relationship between financial sectorcompetition and financial sectoropenness, and between growth and financial sector competition.
Keywords: F40; F13; F43; 330; financial services trade; service trade and imperfect competition; trade in services and growth; Finanzdienstleistung; Internationale Wirtschaft; Welt